Strategi Pengembangan Sekolah Keagamaan Kristen Negeri Unggul: Mengatasi Kesenjangan Pendidikan Keagamaan di Indonesia - Melda Ery Rusmawi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article discusses the urgency of developing a strategy for superior state Christian religious schools as a fundamental solution to address the gap in religious education in Indonesia. Although religious education is guaranteed by the constitution, the reality shows significant disparities, where Christian religious education is still dominated by private institutions with limited funding, facilities, and quality of teaching staff, which stands in stark contrast to state support for similar institutions from other religions. This gap impacts the low competitiveness of graduates, hinders vertical mobility, and has the potential to threaten social harmony. This paper uses qualitative methods with descriptive analysis approaches and USG analysis as well as the theory of William N. Dunn. Starting from these problems, this article identifies several root causes, including unfair resource allocation, the absence of a superior reference model, and the lack of a regulatory framework and integration of a modern curriculum. To address these challenges, this article proposes a comprehensive strategy that includes the development of a holistic curriculum model, guaranteed funding from the state budget, strategic location determination, strengthening supporting regulations, and multi-stakeholder collaboration. With this strategic approach, the development of superior schools will not only improve access to and the quality of Christian religious education, but will also become an instrument for realizing social justice, improving the quality of human resources, and strengthening the foundations of nationality within the framework of Bhinneka Tunggal Ika.